Preconception counselling for low health literate women: an exploration of determinants in the Netherlands - Mirjam P. Fransen; Miriam E. Hopman; Laxsini Murugesu; Ageeth N. Rosman; Sian K. Smith (BMC, 2018)
Abstract Background Women from lower socioeconomic groups tend to be at greater risk of adverse perinatal outcomes, but are less likely to participate in preconception counselling compared to higher socioeconomic groups. This could be partly because of their limited skills to assess, understand and use health related information in ways that promote and maintain good health (health literacy skills). In this study we explored determinants of participation in preconception counselling among women with low health literacy in The Netherlands. Methods Potential determinants of participation in preconception counselling were derived from the literature, and mapped onto a theoretical framework, which was tested for perceived relevance and completeness in an expert review (n = 20). The framework was used to prepare face-to-face interviews with women with low health literacy and a wish to conceive (n = 139). In the interviews we explored preconception counselling awareness, knowledge, considerations, subjective norms, self-efficacy, attitude, and intention. Linear regression analyses were used to test associations with intention to participate in preconception counselling. Results Most women (75%) were unaware of the concept of preconception counselling and the provision of counselling, even if they lived in areas where written invitations had been disseminated. Common considerations for participation were: preparation for pregnancy; perceived lack of information; and problems in a previous pregnancy. Considerations not to participate were mostly related to perceived sufficient knowledge and perceived low risk of perinatal problems. Respondents generally had a positive attitude towards participation in preconception counselling for themselves, and 41% reported that they would participate in preconception counselling. Conclusion Women with low health literacy were generally unaware of the concept and provision of preconception counselling, but seemed to be interested in participation. Further research should investigate how to effectively reach and inform this group about preconception counselling. This knowledge is essential for evidence-based development of interventions to increase the accessibility and understanding of preconception counselling.